Community-Based Tourism (CBT): A Way of Creating and Enhancing the Livelihood of Local People - Nguyễn, Thị Thanh Kiều (Calla) (VNU University, 2023)
Aiming to sustainable development, community-based tourism (CBT) is popular and effective means of the local livelihoods’ enhancement, the preservation of traditional culture values as well as environmental conservation. Therefore, CBT is a form of tourism which has been developed in some remoted areas in Vietnam. The paper explains the role of CBT in the livelihood transformations via tourism activities, analyzes the advantages and disadvantages of CBT development and consequently recommends a number of practical solutions for developing CBT in Vietnam in the forthcoming time. Keywords: CBT, livelihood, local people, Vietnam.